Women's Career Islamic Family Law Perspectives - Jihan Husna Srifyan; Anzar Aquil; Muntaha Artalim Zaim; Abdualhmeed Alqahoom (Walidem Institute and Publishing (WIP), 2023)
The purpose of the study is to analyze the review of Islamic law on the profession and the administration of the wife's salary in Kalipucang Kulon Village, Welahan District, Jepara Regency in supporting family income as a factory worker. This research is a type of field research with a qualitative approach, namely research that has the characteristics that the data is expressed in a natural state or as it is (natural setting), by not changing the shape of symbols or numbers and is descriptive based on the question of how. And the data processing technique is to use qualitative descriptive techniques. Research families that in everyday life have needs that must be met, both primary, secondary and tertiary needs. There are times when a husband does not have enough ability to meet these needs. Therefore, in this time and conditions are different, women have had the same opportunities as men to excel in various areas of life, even economically no longer dependent on men.